Renal Disease in Madeira Islands: Twenty-Seven Years' Experience of Native Kidney Biopsies - Vieira, P (2015)
Introduction: Renal biopsy plays an essential role either in the diagnosis or in the prognosis of patients with renal disease. In order to assess its epidemiology and evolution in Madeira Islands, we analysed twenty-seven years of native kidney biopsies. Methods: We performed a retrospective analysis of clinical records, including histological revision from 1986 to 2012, totalling 315 native kidney biopsies. They were assessed regarding the temporal evolution both for the quality/indications for renal biopsy and for the patterns of kidney disease. Results: A total of 315 native kidney biopsies were analysed. The patients’ mean age was of 40.8 ± 18.4 years and 50.5%(n = 159) were males. The most common indications for renal biopsy were nephrotic syndrome (36.2%, n = 114) and acute kidney injury (20.0%, n = 63). Among primary glomerular diseases (41.5%, n = 115) the most common were IgA nephropathy (26.1%, n = 30) and focal-segmental glomerulosclerosis (17.4%, n = 20) and among secondary glomerular diseases (31.4%, n = 87), lupus nephritis (51.7%, n = 45) and amyloidosis (20.7%, n = 18). Statistical analysis revealed significant correlation between gender and major pathological diagnosis (Fisher’s exact test, p <.01) and between indications for renal biopsy and major pathological diagnosis (χ2, p <.01). Regarding the temporal evolution, no statistically significant differences were found in the number of renal biopsies (χ2, p =.193), number of glomeruli per sample (Fisher’s exact test, p =.669), age (Kruskal-Wallis, p =.216), indications for renal biopsy (χ2, p =.106) or major pathological diagnosis groups (χ2,p =.649). However, considering the specific clinico-pathological diagnoses and their temporal variation, a statistically significant difference (Fisher’s exact test, p <.05) was found for lupus nephritis and membranous nephropathy with an increasing incidence and for amyloidosis with an opposite tendency. Discussion: The review of the native kidney biopsies from a population with particular characteristics, geographically isolated, such as those from Madeira Islands, showed parallel between epidemiological numbers referring to other European subpopulations, allowing simultaneously a comprehensive approach to our renal biopsy policies.